Church robbers and reformers in Germany, 1525-1547 : confiscation and religious purpose in the Holy Roman Empire - Ocker, Christopher (Studies in medieval and Reformation traditions, 2006)
This is a study of the religious controversy that broke out with Martin Luther, from the vantage of church property. The controversy eventually produced a Holy Roman Empire of two churches. This is not an economic history. Rather, the book shows how acceptance of confiscation was won, and how theological advice was essential to the success of what is sometimes called a crucial if early stage of confessional state-building. It reviews the character of sacred property in the late Middle Ages, surveys confiscations in Reformation Germany on illustrative examples, summarizes the League of Schmalkalden's defense of confiscations, systematically studies theological memoranda that shaped a common policy in the League, and shows the role of that common position in religious politics.